Polyether Hexadentate Schiff Base Ligand with Trivalent Chromium, Iron, Cobalt Ions - Ibrahim, Farah M (Al-Nahrain Journal of Science, 2017)
Abstract:Williamson etherification method used to prepared ether compound from salicylaldehyde with 1,3-dibromopropane and potassium carbonate as base, this compound used with 2-amino-4-chlorophenol to prepare polyether hexadentate Schiff base ligand (HSL) by the 1:2 molar condensations. Cr 3+, Fe 3+, Co 3+ ions were reacted with HSL and characterized by 1H NMR and 13CNMR technique, infrared, electronic spectra, elemental analysis, thermal analysis, conductivity and magnetic susceptibility measurements, from results the metal ion was bonded to the HSL through the phenol oxygen, imine nitrogen and ether oxygen atoms to suggest octahedral configurations. The biological activity of HSL with its complexes have been studied.